Development of an international core outcome set for peripheral vascular malformations: the OVAMA project. (14th February 2018) - Horbach, S.E.R.; van der Horst, C.M.A.M.; Blei, F.; van der Vleuten, C.J.M.; Frieden, I. J.; Richter, G.T.; Tan, S.T.; Muir, T.; Penington, A.J.; Boon, L.M.; Spuls, P.I.; ,
Summary: Peripheral vascular malformations (VMs) are birthmarks or swellings caused by the faulty development of blood vessels in the embryo. Different types are classified according to whether the components are mainly lymph vessels (LMs), veins (VMs) or combined arteries and veins (AVMs). It is hard to assess the various medical and surgical treatments available because there are no agreed methods for measuring the outcome. This international group carried out an on‐line survey of health professionals and patients to decide which factors would be important to record in future clinical trials. First they listed aspects of the condition and its treatment in 36 domains covering 97 specific items. Then they asked 167 doctors and 134 patients and parents of patients to score the domains from 0 (not important) to 4 (crucial). The options were progressively narrowed down over 3 rounds of the survey and a consensus conference. The finally agreed "core outcome set" covered: scan results, doctors' assessment of problems caused by pressure from the VM, patient or parent's assessments of symptoms, pain and quality of life, and their satisfaction with the treatment, outcome and any adverse effects. Additional specific factors for LMs were infections and lymphatic fluid leakage, for VMs thrombosis and for AVMs heart function and bleeding. Recurrence after treatment and appearance were also recommended for inclusion. This international consensus establishes what factors should be assessed in future trials of treatments for vascular malformations, but further work is required to decide exactly how they should be measured and reported. Abstract : Linked Article: Horbach et al. Br J Dermatol 2018;178 :473–481